A Systematic Review and Meta-Analysis of B Vitamin Supplementation on Depressive Symptoms, Anxiety, and Stress: Effects on Healthy and ‘At-Risk’ Individuals - Young, Lauren M; Pipingas, Andrew; White, David J; Gauci, Sarah; Scholey, Andrew (Nutrients, 2019)
A systematic review and meta-analysis was undertaken to examine and quantify the effects of B vitamin supplementation on mood in both healthy and ‘at-risk’ populations. A systematic search identified all available randomised controlled trials (RCTs) of daily supplementation with ≥3 B group vitamins with an intervention period of at least four weeks. Random effects models for a standardized mean difference were used to test for overall effect. Heterogeneity was tested using the I2 statistic. Eighteen articles (16 trials, 2015 participants) were included, of which 12 were eligible for meta-analysis. Eleven of the 18 articles reported a positive effect for B vitamins over a placebo for overall mood or a facet of mood. Of the eight studies in ‘at-risk’ cohorts, five found a significant benefit to mood. Regarding individual facets of mood, B vitamin supplementation benefited stress (n = 958, SMD = 0.23, 95% CI = 0.02, 0.45, p = 0.03). A benefit to depressive symptoms did not reach significance (n = 568, SMD = 0.15, 95% CI = −0.01, 0.32, p = 0.07), and there was no effect on anxiety (n = 562, SMD = 0.03, 95% CI = −0.13, 0.20, p = 0.71). The review provides evidence for the benefit of B vitamin supplementation in healthy and at-risk populations for stress, but not for depressive symptoms or anxiety. B vitamin supplementation may particularly benefit populations who are at risk due to (1) poor nutrient status or (2) poor mood status.